Dasar-Dasar dan Sumber Ilmu Pengetahuan - Siola, M. Nasir; Arjul Haq, Ahmad Muflihuddin; Attwar, Muhammad; Anggraeni, Gayatri Fitri; Asmar, Firawati (Socius: Jurnal Penelitian Ilmu-Ilmu Sosial, 2025)
This study aims to provide an in-depth understanding of the fundamental concepts of knowledge, including its definition, sources, types, and the relationship between philosophy of science and the development of scientific knowledge. Knowledge is obtained through scientific methods that can be tested and verified, with a deep philosophical foundation. It encompasses not only empirical observation but also revelation as one of its sources. Truth theories such as coherence, correspondence, and pragmatism are used to evaluate the validity of knowledge. The rapid development of knowledge requires profound understanding to avoid misconceptions and negative impacts. This study emphasizes the importance of the philosophy of science in guiding the systematic and responsible advancement of knowledge.